ANALISIS STRATEGI PENERIMAAN PAJAK BUMI DAN BANGUNAN PEDESAAN DAN PERKOTAAN (PBB P2) SERTA EFEKTIVITAS PENERIMAANNYA DI PEMERINTAH KABUPATEN MINAHASA SELATAN TAHUN 2016-2017 - Tambingon, Vernando Viki; Manossoh, Hendrik; Budiarso, Novi S. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2019)
Based on Law Number 28 of 2009 states that the Land and Building Tax for Rural and Urban Areas is a tax that is controlled by the regional governmentThe purpose of this study was to determine the implementation of the strategy, measure the level of PBB-P2 and countries in South Minahasa Regency in PBB P2 collection. The type of research used is descriptive qualitative data where the primary data to be used will then be analyzed, namely data that can be used for the main purpose of this study.The results of the study indicate that the strategy in UN PBB P2 collection was well implemented, although there were some obstacles in the UN collection process P2. Whereas the acceptance of PBB in P2 in 2016 and 2017 is classified as less effective.